No-till french bean production technology for maize fallow in north-east India - Das, Anup; I., Ramkrushna G.; Layek, Jayanta; Babu, Subhash; Krishnappa, R. (Indian Farming, 2019)
This technology helps in retaining soil moisture with minimum soil disturbance and at the same time reduces the cost of cultivation, save time and meet the increasing demand of green vegetables and pulses in the region. Thus, no-till technology has potential to double the cropping intensity, enhance crop productivity and income of the farmers substantially.